Juegos cooperativos para disminuir el acoso escolar en estudiantes del séptimo año de educación básica paralelo b de la escuela 18 de noviembre - Pozo Ortega, Jennifer Anabel (2018)
The Thesis named: “COOPERATIVE GAMES TO REDUCE SCHOOL, HARASSMENT IN STUDENTS OF THE SEVENTH YEAR OF BASIC EDUCATION, CLASSROOM“B” “FROM 18 DE NOVIEMBRE SCHOOL”. The purpose was to design a plan of activities based on cooperative games to reduce the bullying in the students of the seventh year of basic education, classroom “B”. The research approach is quantitative, the design is preexperimental and the methods used were: scientific, descriptive, analytical-synthetic, deductive-inductive. Also, a Cisneros’s sef-test was applied in a sample of 36 students. The results obtained in the pre-test indicate that in a very high level are the A-scale (contemptridicule) with 53%. The C scale of communication restriction with 44%. Likewise, the F scale of social exclusion-block with 725 while the G scale of verbal harassment with 42% and is located in a high level as well. When applying and evaluating the plan of activities, it was concluded that most of the children presented a decrease in the forms of bullying, standing in a level almost under the A scale with 61% and the C scale with 77%. Additionally, in a very low level the F scale and the G scale with 92%. Thus, it is recommended to continue its application to improve relations between colleagues and the classroom environment.